Hubungan Antara Intensitas Komunikasi Interpersonal Dengan Agresivitas - Rahmat Fitrah Tuasikal (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2008)
The research is aimed to discover relation between the intencity of interpersonal communication and aggressiveness. Subject for this research is student from Psychology of Education and Guidance Program, FKIP UNPATTI, with amount of research subject consist of 86 people.To discover relation between intencity of interpersonal communication with aggressiveness, hence [in] using correlation data analysis of product moment. Result of data analysis show intencity of interpersonal data analysis show intencity of interpersonal communication and aggressiveness have negative correlation and very significant (rxy = -0,460 and p < 0,01).Effective contribution of intencity of interpersonal communication equal to 21,1% to aggressiveness, the rest equal to 78,9% is other factor that have an effect on in this research, even internal factors and also esternal factors.  Key words     : Intensity Communications of Interpersonal, Aggressiveness